What is the Best Route to the Meckel Cave? Anatomical Comparison between the Endoscopic Endonasal Approach and a Lateral Approach - Van Rompaey, Jason; Bush, Carrie; Khabbaz, Eyad; Vender, John; Panizza, Ben; Solares, C. Arturo (Journal of Neurological Surgery Part B: Skull Base, 2013)
Background Traditionally, a pterional approach is utilized to access the Meckel cave. Depending on the tumor location, extradural dissection of the Gasserian ganglion can be performed. An endoscopic endonasal access could potentially avoid a craniotomy in these cases.Methods We performed an endoscopic endonasal approach as well as a lateral approach to the Meckel cave on six anatomic specimens. To access the Meckel cave endoscopically, a complete sphenoethmoidectomy and maxillary antrostomy followed by a transpterygoid approach was performed. For lateral access, a pterional craniotomy with extradural dissection was performed.Results The endoscopic endonasal approach allowed adequate access to the Gasserian ganglion. All the relevant anatomy was identified without difficulty. Both approaches allowed for a similar exposure, but the endonasal approach avoided brain retraction and improved anteromedial exposure of the Gasserian ganglion. The lateral approach provided improved access posterolaterally and to the superior portion.Conclusion The endoscopic endonasal approach to the Meckel cave is anatomically feasible. The morbidity associated with brain retraction from the open approaches can be avoided. Further understanding of the endoscopic anatomy within this region can facilitate continued advancement in endoscopic endonasal surgery and improvement in the safety and efficacy of these procedures.
Keywords: endonasal endoscopic; Gasserian ganglion; lateral approach; maxillary antrostomy; Meckel cave; pterional craniotomy; sphenoethmoidectomy